Noradrenaline protects neurons against H2O2‐induced death by increasing the supply of glutathione from astrocytes via β3‐adrenoceptor stimulation. Issue 2 (20th September 2020) - Yoshioka, Yasuhiro; Negoro, Ryosuke; Kadoi, Hisatsugu; Motegi, Toshiki; Shibagaki, Fumiya; Yamamuro, Akiko; Ishimaru, Yuki; Maeda, Sadaaki
Abstract: Oxidative stress has been implicated in a variety of neurodegenerative disorders, such as Alzheimer's and Parkinson's disease. Astrocytes play a significant role in maintaining survival of neurons by supplying antioxidants such as glutathione (GSH) to neurons. Recently, we found that noradrenaline increased the intracellular GSH concentration in astrocytes via β3 ‐adrenoceptor stimulation. These observations suggest that noradrenaline protects neurons from oxidative stress‐induced death by increasing the supply of GSH from astrocytes to neurons via the stimulation of β3 ‐adrenoceptor in astrocytes. In the present study, we examined the protective effect of noradrenaline against H2 O2 ‐induced neurotoxicity using two different mixed cultures: the mixed culture of human astrocytoma U‐251 MG cells and human neuroblastoma SH‐SY5Y cells, and the mouse primary cerebrum mixed culture of neurons and astrocytes. H2 O2 ‐induced neuronal cell death was significantly attenuated by pretreatment with noradrenaline in both mixed cultures but not in single culture of SH‐SY5Y cells or in mouse cerebrum neuron‐rich culture. The neuroprotective effect of noradrenaline was inhibited by SR59230A, a selective β3 ‐adrenoceptor antagonist, and CL316243, a selective β3 ‐adrenoceptor agonist, mimicked the neuroprotective effect of noradrenaline. DL‐buthionine‐[S, R]‐sulfoximine, a GSH synthesis inhibitor, negated the neuroprotective effect of noradrenaline in both mixed cultures. MK571, which inhibits the export of GSH from astrocytes mediated by multidrug resistance‐associated protein 1, also prevented the neuroprotective effect of noradrenaline. These results suggest that noradrenaline protects neurons against H2 O2 ‐induced death by increasing the supply of GSH from astrocytes via β3 ‐adrenoceptor stimulation. Abstract : Noradrenaline stimulates β3 ‐adrenoceptor in astrocytes and increases the supply of glutathione from astrocytes to neurons, thereby increasing the intracellular glutathione concentration in neurons and protecting them from H2 O2 ‐induced cell death.